Effect of internal noise on the relaxation time of an yttria stabilized zirconia-based memristor. (March 2022) - Filatov, D.O.; Koryazhkina, M.N.; Novikov, A.S.; Shishmakova, V.A.; Shenina, M.E.; Antonov, I.N.; Gorshkov, O.N.; Agudov, N.V.; Carollo, A.; Valenti, D.; Spagnolo, B.
Abstract: The effects of temperature on the switching kinetics of an yttrium-stabilized zirconia-based memristor from a low-resistance state to a high-resistance state have been experimentally investigated. It was found that the memristor relaxation time depends on the temperature in a non-monotonous way, with a maximum observed at the temperature close to 55 °C. This nonmonotonic behavior is a signature of the noise-enhanced stability phenomenon observed in all physical and complex systems characterized by metastable states.